Income from Urban Farming Beans ( Phaseolus vulgaris L. ) in Benpasi Village, Kefamenanu City District - Umbu Joka; Aprianus Nelson Bana (Agribusiness Journal, 2021)
Through a survey approach in June 2020, this study intends to (1) determine the general description; (2) determine income; and (3) calculate the relative advantages of urban farming of chickpeas in the Nekaf Mese farmer group in Benpasi Village, Kefamenanu City District, North Central Timor Regency. The research respondents were chosen from a purposive sample of 20 farmers who were members of farmer groups. The quantitative descriptive method was employed to find out. The findings revealed that bean farmers in Benpasi Village, particularly in the Nekaf Mese Farmer Group, grow their own land, ranging in size from 6 to 9 acres, and engage in all stages of urban farming, including seed preparation, land preparation, planting, maintenance, harvesting, and post-harvest. Farmers' overall revenue from farming activities is Rp. 36.550.000,- with an average of Rp. 1,827,500,- for one planting season, and the total income earned is Rp. Rp. 15,921,000, - with an average income of Rp. 796,050, - for a single planting season. Farmers in the Nekaf Mese Farmer Group, Benpasi Village, Kefamenanu City District, made an average relative profit of 1.74 in bean farming activities, which means that the bean farming activities carried out by farmers in the Nekaf Mese Farmer Group, Benpasi Village, Kefamenanu City District, made an average relative profit of 1.74 in bean farming activities. Because the computation results are more than 1, it can be economically profitable.